The Use Of Mobile Applications For Reproductive Health Education And Family Planning With Participatory Learning and Action (PLA) Method Among Couples Of Child-Bearing Age - WAHYUNI, CANDRA (Journal of Community Engagement in Health, 2025)
The rapid development of information technology has significantly affected various aspects of life, including reproductive health and family planning. One innovative approach in this area is the development of mobile apps specifically designed to help couples of childbearing age access accurate, practical, and easy-to-use information. This community service program is implemented to strengthen knowledge, attitudes, and practices related to reproductive health through the use of a mobile app that integrates three important features: a fertility calculator, a contraceptive method guide, and interactive discussions. The fertility calculator allows users to monitor the menstrual cycle, determine fertile and infertile periods, and support pregnancy planning and prevention of unwanted pregnancies. This contraceptive guide provides comprehensive information about the various methods available, including hormonal and non-hormonal options, along with their benefits, side effects, and suitability for a variety of health conditions. Discussion forums create a safe platform for couples to share experiences, ask questions, and receive support from peers and healthcare professionals. Together, these features are expected to increase users' confidence and independence in making decisions. This program uses a community approach, Participatory Learning and Action  (PLA) model. A total of 25 couples of childbearing age participated in this program. The results showed a significant increase in participant knowledge, with the average score increasing from 55.2% before the intervention to 82.4% after the intervention. In conclusion, the use of mobile applications in reproductive health education and family planning has been shown to be effective